EXPLORING STUDENTS' MOTIVATION IN LEARNING ENGLISH THROUGH DIGITAL-BASED INSTRUCTION IN INDONESIAN EFL SCHOOL CONTEXTS - Cempa Huzaimah; Inayatul Muntaqiyah (Sensei International Journal of Education and Linguistic, 2023)
Students' motivation remains a central issue in English as a foreign language learning because it influences their willingness to participate, persist, communicate, and develop autonomous learning habits. In many classroom contexts, students still perceive English as difficult, distant from daily communication, and strongly associated with examination pressure. Digital-based instruction offers opportunities to increase motivation by providing multimodal input, interactive tasks, immediate feedback, flexible access, and more authentic exposure to English. However, the motivational role of digital instruction depends on how students experience the learning process, not merely on the presence of technology. This study aims to explore students' motivation in learning English through digital-based instruction in Indonesian EFL school contexts. A qualitative case study design was employed. Data were collected through semi-structured interviews, focus group discussions, classroom observations, students' reflective journals, and learning document analysis. The participants consisted of 36 junior secondary students and two English teachers. The data were analyzed thematically. The findings revealed four major themes: digital-based instruction increased situational interest, supported learner autonomy, strengthened confidence through feedback and peer interaction, and created motivational tensions related to distraction, access, fatigue, and English anxiety. The study concludes that digital-based instruction can enhance students' motivation when digital tools are pedagogically structured, emotionally supportive, interactive, and aligned with students' language needs. Technology should therefore be treated as a motivational mediator rather than as an automatic solution for English learning.